Efektivitas Penggunaan Warna Lampu Celup Bawah Air yang Berbeda Terhadap Hasil Tangkapan Bagan Apung di Perairan Teluk Lande Kabupaten Buton Selatan - Fina Miranti; Hasnia Arami; Syamsul Kamri; Muslim Tadjuddah; Abdullah Abdullah (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2022)
Floating lift net is a fishing gear that is classified into the lift net group. The main parts of the floating liftnet are the net, the liftnet house, and the lights as attractor . In addition to the strength of the light, it is believed that the color of the light will affect the fish's response considering that the visual abilities of each type of fish are different. Based on this, this research was conducted to know: 1) the number of catches using different underwater light colors; 2) the effectiveness of each color of light on the catch. The research was conducted from May to June 2022 in Lande Bay, Gerak Makmur Village, South Buton. The research was carried out using experimental fishing methods by conducting 15 attempts of catching alternately on 2 underwater light colors (yellow and blue). The results showed that the total catch for the yellow lights was 66.808 kg (72%) and the blue ones were 25.650 kg (28%). There were 10 species of fish caught consisting of 10 species caught on yellow lights and 9 species caught on blue lights. The three types of fish that were dominant in the 2 colors of the lights were anchovies (Stolephorus Sp), sardinella (Sardinella Sp), bigeye scad (Selar crumenophthalmus). Based on the proportion of total weight, it shows that the yellow dye is more effective (72%), compared to the blue dye (28%).